2018
DOI: 10.1136/bcr-2017-222373
|View full text |Cite
|
Sign up to set email alerts
|

Case of acute mixed liver injury due to hypothyroidism

Abstract: The effects of hypothyroidism on the liver are not well understood. A 77-year-old woman with Hashimoto's thyroiditis had stopped taking levothyroxine on her own for 6 months. Her thyroid stimulating hormone (TSH) level was consistent with severe hypothyroidism. She resumed thyroid replacement therapy. The following month, her liver function tests were significantly elevated. Seven weeks after resumption of therapy, her TSH and liver tests had returned to normal. We attribute the mixed hepatocellular injury to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…However, liver dysfunction also occurred in those with normal thyroid function as shown in the present patient and in the previous literature [4,26]. Duong et al reported a case of acute mixed liver injury due to hypothyroidism [27]. These cases remind us that the safe dose range of thyroid hormone is narrow, and that a stable and normal state of thyroid function is critical for human health.…”
Section: Discussionsupporting
confidence: 82%
“…However, liver dysfunction also occurred in those with normal thyroid function as shown in the present patient and in the previous literature [4,26]. Duong et al reported a case of acute mixed liver injury due to hypothyroidism [27]. These cases remind us that the safe dose range of thyroid hormone is narrow, and that a stable and normal state of thyroid function is critical for human health.…”
Section: Discussionsupporting
confidence: 82%
“…Aside from occasionally mildly elevated liver enzymes (ALP, ALT), a specific association between hypothyroidism and clinically apparent hepatopathy has not been extensively described in the veterinary literature; however, an association between hypothyroidism and gallbladder mucoceles is well described in dogs [16,17]. Several case reports in human medicine highlight an association between hypothyroidism, hepatic disease, and hyperammonemic coma, with at least one report of acute hypothyroid-induced mixed hepatopathy [18][19][20]. Cage-side measurement of ammonia is less commonly performed in veterinary medicine, and thus, the ammonia status of the presented case is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the good knowledge of the effect of thyroid hormones on the entire human metabolism, the effects of hypothyroidism on the liver are not always well understood [13]. However, minim liver injuries and/or minim to moderate abnormalities of hepatic enzymes are often frequently associated to thyroid diseases [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, most cases of hypertransaminasemia caused by hypothyroidism are reported as sporadic observations [9,11,12,19,20]. These hypertransaminasemias may be isolated or may be associated with cholestasis defining mixed hepatic injury [13] or more rarely integrate into the setting of more severe clinical presentation with hyperammonemia [21] or severe hepatic insufficiency with hepatic encephalopathy [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation